(3GdSdY GdYGeI GdOhdjI (B:s (3GdMhGaR, GdbjGS hGdJehjd (B/s - (3ajQhfj, eGQchs; (3ehOj, CThcGs ((3HjQhJ(B: s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B, s, 2004)
(3GdMhGaR GdYGdejI ddSdY GdYGeI GdOhdjI(B- (3JYQja GdSdY GdYGeI GdOhdjI(B- (3GdSdY GdYGeI GdOhdjI hGdeDKQGJ GdNGQLjI(B- (3CfhGY GdefGaY GdYGeI hGdSdY GdYGeI(B- (3GdeVGejf GdeGdjI HGdfSHI ddOhd GdfGejI(B- (3JRhjO GdSdY GdYGeI GdOhdjI(B- (3GdMhGaR dJhajQ GdSdY GdYGeI GdOhdjI(B- (3GdJYQa Ydi GdJMOjGJ JhajQ GdSdY GdOhdjI GdGSGSjI(B- (3BdjGJ GdJehjd dJMbjb GdJfSjb(B- (3Jehjd GdSdY GdYGeI GdOhdjI(B- (3JNUjU GdeSGYOGJ dSdY GdYGeI GdOhdjI(B- (3GdSdY GdYGeI GdhWfjI aj eSGYOGJ GdJfejI GdQSejI(B- (3Jehjd GdSdY GdEbdjejI(B.s
Keywords: (3GdJehjds; (3GdJehjd GdOhdjs; (3GdSdYs